Flexural behavior of timber-high-performance concrete experimental slabs - Tomáš Vlach; Jonáš Klimt; Eliška Kafková; Jan Macháček; Věra Kabíčková; Jakub Hájek (Acta Polytechnica CTU Proceedings)
In general, one of the possible future paths of the building construction industry is the development of robotization and prefabrication of individual building components. Presented article continues the development of prefabrication using traditional effective ombination of two often used materials in construction – timber and concrete in the form of a slabs. The traditional concept of combining these materials is used for ceiling structures – slabs, panels, floor panels, where timber is most often in the form of beams and a concrete slab is applied over the beams as a material transmitting compressive stress. The key to functionality for this system is the shear connection of both materials. The presented study presents a thin concrete layer made of high-performance concrete, which is connected to a wooden board from glulam using an adhesive bridge. The aim of this presented study is to improve the bending load-bearing capacity and bending stiffness of the glulam slab with a small amount of high-performance concrete and thus achieve a more favorable environmental profile of the ceiling panel. The individual variants differ in thickness, the presence and number of ribs. These variants are compared with a variant of the same thickness of glulam slab without the layer of concrete.